Cloning and sequencing of a cluster of genes encoding branched-chain alpha-keto acid dehydrogenase from Streptomyces avermitilis and the production of a functional E1 [alpha beta] component in Escherichia coli. - Skinner, D D (1995)
A cluster of genes encoding the E1 alpha, E1 beta, and E2 subunits of branched-chain alpha-keto acid dehydrogenase (BCDH) of Streptomyces avermitilis has been cloned and sequenced. Open reading frame 1 (ORF1) (E1 alpha), 1,146 nucleotides long, would encode a polypeptide of 40,969 Da (381 amino acids). ORF2 (E1 beta), 1,005 nucleotides long, would encode a polypeptide of 35,577 Da (334 amino acids). The intergenic distance between ORF1 and ORF2 is 73 bp. The putative ATG start codon of the incomplete ORF3 (E2) overlaps the stop codon of ORF2. Computer-aided searches showed that the deduced products of ORF1 and ORF2 resembled the corresponding E1 subunit (alpha or beta) of several prokaryotic and eukaryotic BCDH complexes. When these ORFs were overexpressed in Escherichia coli, proteins of about 41 and 34 kDa, which are the approximate masses of the predicted S. avermitilis ORF1 and ORF2 products, respectively, were detected. In addition, specific E1 [alpha beta] BCDH activity was detected in E. coli cells carrying the S. avermitilis ORF1 (E1 alpha) and ORF2 (E1 beta) coexpressed under the control of the T7 promoter.